IN VITRO RESPONSE OF AZADIRACHTA INDICA TO SALINITY STRESS AND ITS EFFECT OF CERTAIN OSMOPROTECTANTS AND ANTIOXIDATIVE ENZYMES - M.B SHIVANNA; B.R NAGASHREE; B.R. GURUMURTHY (International Journal of Pharma and Bio Sciences, 2013)
Azadirachta indica is an important multipurpose social-forestry species moderately tolerant to salinity stress. There is an increase in the demand for saline tolerant lines of neem. In the present study, a tissue culture method was optimized to obtain callus and regenerates from nodal explants and exposed them to different levels of saline concentration in MS were selected for the determination of biochemical parameters. Increase in salinity caused a reduction in proliferation of calli and shoot growth and regeneration frequency. Proline, glycine betaine and peroxidase contents of calli and regenerated shoots increased with increase in salinity up to 150 and 200 mM, respectively. The catalase activity in the calli and regenerated shoot increased up to 150 mM saline and declined thereafter. These findings indicated that A. indica exhibited protection against the oxidative damage caused by salinity up to 250 mM, at least partly, due to constitutive and induced activities of antioxidative enzymes.